2018
DOI: 10.1039/c8ra02879f
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative functionalization of aliphatic and aromatic amino acid derivatives with H2O2 catalyzed by a nonheme imine based iron complex

Abstract: Amino acid derivatives are oxidized by the 1/H2O2 system. A marked preference for the aromatic over Cα–H and benzylic C–H oxidation is observed with phenylalanine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…reported an iminopyridine iron complex capable of oxidizing aromatic substrates, as well as aromatic amino acids, under mild reaction conditions (Figure 1). [3g,6] However, for all these examples, aromatic oxidation of alkylbenzenes is effectively accompanied by benzylic hydroxylation. In addition, recently reported nickel, copper and cobalt complexes supported by aminopyridine ligands accomplished the oxidation of benzene to phenol in improved yields (29–41%) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…reported an iminopyridine iron complex capable of oxidizing aromatic substrates, as well as aromatic amino acids, under mild reaction conditions (Figure 1). [3g,6] However, for all these examples, aromatic oxidation of alkylbenzenes is effectively accompanied by benzylic hydroxylation. In addition, recently reported nickel, copper and cobalt complexes supported by aminopyridine ligands accomplished the oxidation of benzene to phenol in improved yields (29–41%) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Di Stefano and co-workers have reported a series of papers based on iron complexes of tridentate N3 imine ligands. For instance, the in situ prepared Fe­(II) complex ( 18 ) (Figure ) catalyzed benzene hydroxylation with H 2 O 2 and the phenol yield reached 23% along with 5% of p- benzoquinone . In 2014, a few Fe­(III) complexes 19a , 19b , and 20 (Figure ) of reduced Schiff base tridentate N3 ligands were employed for benzene oxidation .…”
Section: Homogeneous Transition Metal Complexes In Benzene Hydroxylationmentioning
confidence: 99%
“…Along this line good results have been obtained in the aromatic oxidation catalyzed by heme and non-heme metal complexes which are biomimetic models of natural oxygenases, although most of them are stoichiometric transformations. We have recently reported that the iminopyridine complex 1, easily obtained by in situ self-assembly of 2-picolylamine, 2picolylaldehyde and iron(II) triflate in a 2:2:1 ratio in acetonitrile (Scheme 1) [32][33][34][35][36] efficiently catalyzes the hydroxylation of aromatic rings with H2O2 under mild conditions. [37] Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…[4,[8][9][10]24] In this context it is interesting to note that the The1/H2O2 system allowed the direct conversion of phenylalanine to tyrosine isomers without overoxidation or side-chain functionalization. [36] In order to gain more insight into this high chemoselectivity and define its potential, in this work we focused our attention on the oxidation chemoselectivity of polycyclic alkylaromatic substrates containing more reactive benzylic C-H bonds characterized by relatively low BDE values (75-82 kcal/mol, Chart 1). [59] Chart 1.…”
Section: Introductionmentioning
confidence: 99%